ANALISIS KEBANGKRUTAN Z SCORE ALTMAN PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN DI MASA PANDEMI - Moch. Wahyu Widodo; Sigit Wisnu Setya Bhirawa; Wibiyanti, Wynda (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to predict the bankruptcy of the automotive and component sub-sector manufacturing companieslisted on the IDX for the 2020 period using the Altman Z Score. In this study, the population used is theautomotive and component manufacturing sub-sector companieslisted on the IndonesiaStockExchange (IDX) inthe period 2020. In determining the sample using purposive sampling, namely by showing directly to a populationbased on the characteristics or characteristics of the sample, with the aim of obtaining a representative sample inaccordance with the specified criteria. The steps taken in data collection using documentation techniques arecarried out by finding and collecting secondary data. The results showed that the condition of the automotive andcomponent sub-sector manufacturing companies according to Altman's Z Score assessment was in the distresszoneclassification.   Keywords: Failure, ZScoreAltman